2014
DOI: 10.1259/bjr.20130770
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study on energy prediction of microwave ablation upon uterine adenomyosis and leiomyomas by MRI

Abstract: Objective: To evaluate the feasibility of energy prediction of percutaneous microwave ablation (PMWA) upon uterine leiomyomas and adenomyosis by MRI. Methods: 63 patients (49 patients with 49 uterine leiomyomas and 14 patients with adenomyosis) who underwent ultrasound-guided PMWA treatment were studied during the period from June 2011 to December 2012. Before PMWA, contrast-enhanced MRI (ceMRI) was performed for all of the patients. Based on the signal intensity (SI) of T 2 weighted MRI, uterine leiomyomas we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…US-guided percutaneous microwave ablation (PMWA) therapy utilises electromagnetic microwave heat to induce cellular death via coagulation necrosis. Single-centre research studies have confirmed the safety and efficacy of this treatment; it has been shown that this treatment is effective, minimally invasive and uterus-conserving with effective relief of clinical symptoms after therapy [4][5][6][7][8][9][10][11]. However, no multicentre study with a large sample has been conducted to confirm the conclusions of these single-centre investigations.…”
Section: Introductionmentioning
confidence: 99%
“…US-guided percutaneous microwave ablation (PMWA) therapy utilises electromagnetic microwave heat to induce cellular death via coagulation necrosis. Single-centre research studies have confirmed the safety and efficacy of this treatment; it has been shown that this treatment is effective, minimally invasive and uterus-conserving with effective relief of clinical symptoms after therapy [4][5][6][7][8][9][10][11]. However, no multicentre study with a large sample has been conducted to confirm the conclusions of these single-centre investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Ensuring the efficiency of treatment without negatively affecting ovarian function remains a longstanding challenge in these patients 4 . Ultrasound (US)-guided percutaneous microwave ablation (PMWA) has been used in the treatment of symptomatic adenomyosis and fibroids 5 6 7 8 9 , which has produced satisfactory clinical outcomes. However, changes in serum hormone levels after PMWA have not been thoroughly studied.…”
mentioning
confidence: 99%
“…The UPMWA treatment protocol was based on previously published protocols 5 6 7 8 9 10 11 . In brief, ablation was performed under conscious intravenous sedation (intravenous infusion of flurbiprofen ester 2 mg/kg, supplemented by pumping 4 mg/(kg·h) –1 propofol).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, treatment goals include not only alleviation of the symptoms, but also reservation or even amendment of the ability of fertility. Recently, ultrasound-guided percutaneous microwave ablation (UPMWA) has been widely used to treat symptomatic myomas and adenomyosis 5 6 7 8 9 10 11 . This has been shown to be a feasible and safe approach for treating symptomatic uterine fibroids; moreover, the procedure is easy, fast, and minimally invasive.…”
mentioning
confidence: 99%